The impact of family income on child achievement: Evidence from the earned income tax Credit - Gordon B. Dahl; Lance Lochner (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2010)
Past estimates of the effect of family income on child development have often been plagued by endogeneity and measurement error. In this paper, we use an instrumental variables strategy to estimate the causal effect of income on children's math and reading achievement. Our identification derives from the large, non-linear changes in the Earned Income Tax Credit (EITC) over the last two decades. The largest of these changes increased family income by as much as 20%, or approximately 2,100, between 1993 and 1997. Using a panel of roughly 4,500 children matched to their mothers from National Longitudinal Survey of Youth datasets allows us to address problems associated with unobserved heterogeneity, endogenous transitory income shocks, and measurement error in income. Our baseline estimates imply that a 1,000 increase in income raises combined math and reading test scores by 6% of a standard deviation in the short-run. Test gains are larger for children from disadvantaged families and are robust to a variety of alternative specifications.
Keywords: 330; Familie; Haushaltseinkommen; Kinder; Steuerbegünstigung; Bildungsverhalten; Bildungsniveau; USA